Disrupting MALAT1/miR-200c sponge decreases invasion and migration in endometrioid endometrial carcinoma. Issue 1 (1st December 2016) - Li, Qiulian; Zhang, Chao; Chen, Ruichao; Xiong, Hanzhen; Qiu, Fuman; Liu, Shaoyan; Zhang, Minfen; Wang, Fang; Wang, Yu; Zhou, Xuan; Xiao, Guohong; Wang, Xudong; et al.
Abstract: Endometrioid endometrial carcinoma (EEC) is the most common gynecologic malignancy around the world. Epithelial-to-mesenchymal transition (EMT) is a core process during EEC cell invasion. The abnormal expression of the long noncoding RNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) or miR-200 family members were shown to facilitate EMT in multiple human cancers, but the regulatory mechanism by which MALAT1 and miR-200 act remains unknown. Previous studies have shown that miR-200 family members are enriched in EEC as well as melanoma and some ovarian carcinomas. In the present study, we first showed that miR-200c levels were higher in most EEC specimens than in non-tumor tissues, while MALAT1 levels were lower. Moreover, we found that miR-200c bound directly to MALAT1 using luciferase reporter and qRT-PCR assays. MALAT1 and miR-200c are reciprocally repressed, and TGF-β increased MALAT1 expression by inhibiting miR-200c. When the interaction between miR-200c/MALAT1 was interrupted, the invasive capacity of EEC cells was decreased and EMT markers expression were altered in vitro . A xenograft tumor model was used to show that targeting the miR-200c/MALAT1 axis inhibited EEC growth and EMT-associated protein expression in vivo . In summary, miR-200c/MALAT1 axis is a target with therapeutic potential in EEC. However, different expression model of miR-200c and MALAT1 in EEC with that in other organ carcinomas needs further mechanism researches. Highlights: The relationship of miR-200c and MALAT1 expression is reverse in EEC. miR-200c binds to MALAT1 and forms MALAT1/miR-200c sponge in EEC. MALAT1 and miR-200c are reciprocally repressed. Targeting miR-200c/MALAT1 could inhibit EMT, invasion and cytoskeleton remodeling in EEC.